Pedagogi Tasawuf Dalam Pendidikan Islam Moderat - al-Chudri, M. Ridho Maulana; Najib, Ainun (YASIN, 2025)
This study examines the concept of Sufi pedagogy in the context of moderate Islamic education, using a qualitative approach and the PRISMA systematic review method approach. Sufi pedagogy is researched as a multidimensional approach that integrates spiritual, social, and technological competencies in shaping students' character. This research explores how moderate Islamic education incorporates values such as justice, tolerance, and empathy into the curriculum to foster a generation that aligns faith and knowledge. These findings reveal that Sufi pedagogy provides a viable solution to contemporary moral and ethical challenges while allowing students to adapt to modern technological advances without losing the essence of Islamic values. By instilling spiritual awareness alongside intellectual growth, this pedagogical model nurtures individuals who are not only well-informed but also have a strong ethical and moral foundation. In an era dominated by artificial intelligence and digital learning, Sufi pedagogy offers a unique bridge between tradition and modernity. Its integration into Islamic education ensures that students are equipped with religious awareness and practical life skills. From this pedagogical approach can contribute to forming a generation that is morally responsible and intellectually competent, ready to navigate the complexities of the modern world.